Religiosity as a Mediator of Social Support for the Employee Engagement of Female Lecturers in Long-Distance Marriages - Ali Syahidin Mubarok; Mirna Wahyu Agustina (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Long-distance marriage has several risks, but some couples decide to undergo this condition for various reasons, one of which is their work career. This research aims to look at employee engagement among female lecturers in long-distance marriages by using social support as a predictor and religiosity as a mediator. This research uses a quantitative approach with a simple mediation analysis. The population in this study were female lecturers who were in long-distance marriages for at least one-year. There were 54 participants in this study using total sampling who had undergone a long-distance marriage. Data were collected using a questionnaire with a Likert scale containing four answer choices. The instruments in this study used adaptations of the Multidimensional Scale of Perceived Social Support (MSPSS), Centrality of Religious Scale (CRS) and Employee Engagement Scale (EES). Data were analyzed using regression analysis. Meanwhile, the research results show a direct effect of social support on employee engagement and the influence of religiosity on employee engagement. These results show that religiosity is a partial mediator of employee engagement. This study suggests that female lecturer who undergoes a long-distance marriage can reach their best career when they get support from any circle she has and upgrade their religiosity. This study also showed if religiosity could have an effect on increasing employee engagement as a responsibility for the job.